The psychology of criminal and violent behaviour - Lyon, David R. (OUP Canada, 2017)
"The Psychology of Criminal Behaviour is a thrilling and comprehensive introduction to the psychological theories of criminality and violence. It examines how psychology and biology both play a role in understanding what may lead individuals to commit crime. Theoretical in approach, The Psychology of Criminal Behaviour ensures that material is presented in a way that meets the needs of both psychology and criminology students. The text includes exciting case studies and research boxes, chapter introductions and summaries, a marginal glossary, and thoughtful review questions to enhance student understanding and engagement. From genetic influences to developmental theories, serial killers to stalkers, the text applies relevant research and real-world examples, creating an exciting and inclusive introduction to the field."--